Social acceptance of students with Down syndrome and students without disability. Issue 8 (13th September 2016) - Schwab, Susanne; Huber, Christian; Gebhardt, Markus
Abstract : We investigated the influence of teacher feedback on the social acceptance of peers with intellectual disabilities and peers without disabilities. A computer task was administered to 601 students in grades 3 and 4. Twenty-six per cent of the students attend an inclusive school; the others are in regular schools without students with special educational needs. Participants are introduced to 'new' virtual classmates, one student with Down syndrome (DS), and one control student with no obvious disability. Additionally, teacher feedback and feedback about fun playing with the new classmates is given. Social acceptance is evaluated by asking if one would like to sit next to him/her. Both feedbacks showed a strong effect. The child with DS was less socially accepted than the child without disability. No difference regarding the social acceptance of the students with DS was found between students from inclusive and regular classes. Students from regular classes rate the social acceptance of the student without disabilities significantly higher than students from inclusive classrooms.